P103 Antibiotic use and comorbid pleural infection in patients with malignant pleural effusion. (12th November 2019) - George, V; Mercer, R; Bedawi, E; Dudina, A; Rahman, N
Abstract : Introduction and objectives: Malignant pleural effusion (MPE) affects 15% of all patients with cancer. (1) Despite this, diagnosis can be difficult and patients are often treated with antibiotics for presumed pleural infection. While many of these cases represent initial misdiagnosis, there is a subset of patients with MPE who have comorbid infection at presentation. We attempted to quantify the proportion of patients with MPE who receive antibiotics at presentation, and evaluate how many had evidence of pleural infection. Methods: All pleural fluid samples collected at our centre over the 3 years prior to December 31 2017 were retrospectively reviewed. Patients with MPE were examined to identify those that received antibiotics for pleural infection prior to their pathological diagnosis. The pleural fluid chemistry and microbiology and response to treatment were then reviewed. Results: 1352 pleural fluid samples were collected over the 3-year period in 1061 patients. 335 of these individuals were diagnosed with MPE. Preliminary analysis of 67 cases demonstrated that 15 (22%) received antibiotics during hospital presentation with effusion. Of these, none had positive pleural microbiology or macroscopic pus, 1 (6.6%) had a pH <7.20, and 4 (26.6%) had a glucose <3.3 mmol/L. Three individuals received a 4–6 week course of antibiotics for presumed comorbid empyema, with 1 demonstrating a significant reduction in inflammatory markers. The remaining 12 (80%) received shorter courses of antibiotics, without clear evidence of infection. Conclusions: MPE presents with non-specific symptoms and patients can often have raised inflammatory markers. Even in the tertiary setting our ability to promptly and accurately differentiate malignancy from pleural infection is poor and often leads to unwarranted antibiotic therapy. This is likely to be associated with diagnostic delay, antibiotic related morbidity and increased healthcare costs. In most cases presumptive treatment is commenced well before the involvement of specialist pleural services. Increased education of frontline staff and new strategies, such as the routine addition of serum procalcitonin and increased acquisition of pleural biopsies, should now be studied. Reference: Clive AO, Jones HE, Bhatnagar R, Preston NJ, Maskell N. Interventions for the management of malignant pleural effusions: a network meta-analysis (Review). 2018;(5).